The 100 - Morgan, Kass. (New York, NY : Little, Brown and Co., 2014)
When one hundred juvenile delinquents are sent on a mission to recolonize Earth, they get a second chance at freedom, friendship, and love, as they fight to survive in a dangerous new world.
School Library Journal, November 2013
Publisher's Weekly, August 2013
Booklist, September 2013
Horn Book, April 2014
Library Media Connection, March 2014
Young Adult
Keywords: Survival -- Juvenile fiction; Juvenile delinquents -- Juvenile fiction; Survival -- Fiction; Juvenile delinquents -- Fiction; Science fiction; Survival skills -- Fiction; Juvenile delinquency -- Fiction; Science fiction; Science fiction